2016
DOI: 10.5713/ajas.15.0011
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Adipogenic Genes in Adipose Tissues of Feedlot Steers Fed Supplementary Palm Oil or Soybean Oil

Abstract: We hypothesized that supplementing finishing diets with palm oil would promote adipogenic gene expression and stearoyl-CoA desaturase (SCD) gene expression in subcutaneous (s.c.) and intramuscular (i.m.) adipose tissues of feedlot steers. Eighteen Angus and Angus crossbred steers were assigned to three groups of 6 steers and fed a basal diet (control), with 3% palm oil, or with 3% soybean oil, for 70 d, top-dressed daily. Tailhead s.c. adipose tissue was obtained by biopsy at 14 d before the initiation of diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…As in our study with Angus crossbred cattle (Choi et al , 2016), supplemental palm oil decreased C/EBPß gene expression and caused a small decrease in SCD gene expression. The marked increase in AMPKα gene expression in i.m.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…As in our study with Angus crossbred cattle (Choi et al , 2016), supplemental palm oil decreased C/EBPß gene expression and caused a small decrease in SCD gene expression. The marked increase in AMPKα gene expression in i.m.…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, supplemental palm oil decreased the SCD index (ratio of palmitoleic acid:stearic acid) from 0.49 to 0.32 in the previous study (Choi et al , 2016) and from 0.39 to 0.34 in the current study. Adipose tissue is the primary site for SCD activity (St John et al , 1991) and SCD gene expression increases with time on a finishing diet (Adams et al , 2010).…”
Section: Discussionsupporting
confidence: 68%
“…The functionality of pSCD1 in SK6 and SK6‐I‐ pSCD1 cells was assessed by fatty‐acid analysis in the absence or the presence of supplemental palmitic acid and an inhibitor of SCD1 activity. We previously had demonstrated that supplemental palmitic acid enhanced bovine SCD1 gene expression, putatively through interaction with the intrinsic SCD1 promoter (Choi et al, ). Therefore, we first established the effect of supplemental palmitic acid and SCD1 inhibitor treatment in SK6 and SK6‐I‐ pSCD1 cells on pSCD1 gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…In animals fed palm oil, the expression of AMP-activated protein kinase alpha (AMPKα) decreased in subcutaneous adipose tissue, while the mRNA level of CCAAT enhancer binding proteinbeta (CEBPβ) reduced in both adipose depots. The soybean oil led to a decreased SCD transcript level in the subcutaneous adipose more effectively than did the palm oil, undermining the original hypothesis, which assumed the crucial role of palm oil in promoting adipogenesis (Choi et al 2016). The n-3 PUFA-enriched fish oil diet in cattle also reduced the expression of SCD and SREBF1 genes in muscle, though the expression of both genes was positively correlated with n-6 PUFA muscle content (Waters et al 2009).…”
Section: Beef Ruminants Postnatal Feeding: Starch Sourcementioning
confidence: 87%
“…Beef ruminants postnatal feeding: fat source Differences in the composition and content of fatty acid in an experimental diet can alter the fatty acid profile in the beef via changes to the lipid metabolism gene expression, which could result in benefits as healthier meat. The effect of oil supplementation on cattle has been studied by Choi et al (2016), who supplied animals with soybean oil (rich in PUFA) and palm oil (high in oleic acid) on the assumption that the palm oil would promote the expression of adipogenic genes in subcutaneous and intramuscular adipose depots. In animals fed palm oil, the expression of AMP-activated protein kinase alpha (AMPKα) decreased in subcutaneous adipose tissue, while the mRNA level of CCAAT enhancer binding proteinbeta (CEBPβ) reduced in both adipose depots.…”
Section: Beef Ruminants Postnatal Feeding: Starch Sourcementioning
confidence: 99%